2015
DOI: 10.23960/jsl3351-62
|View full text |Cite
|
Sign up to set email alerts
|

Motivasi Petani Dalam Mengelola Hutan Rakyat Di Desa Sukoharjo 1 Kecamatan Sukoharjo Kabupaten Pringsewu

Abstract: Lampung Province is one province in Indonesia has deforestation for about 600 hactare in a year (Pusdaling, 2013). This leads to the decline of the quality and quantity of forest. That condition is inversely of Sukoharjo 1 Village Sukoharjo District Pringsewu Regency, the development in that village more than 200 hectar through the private forest development. The purpose of this research were to know the level of motivation farmers and the factors that influence the motivation farmers in managing private fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
3
0
6
Order By: Relevance
“…This is evident from the fact that even though the price of cabbage tended to fall, these farmers were still willing to cultivate cabbage. This result is in line as that of a research by [13] that the suitability level of Mendong plants with the local culture was high because the farmers considered Mendong plants to be ancestral heritage that had to be preserved. This is evident from the fact that even though the land area reduced and the price of mendong fell, the farmers continued to cultivate it.…”
Section: Relatedness Needssupporting
confidence: 90%
See 1 more Smart Citation
“…This is evident from the fact that even though the price of cabbage tended to fall, these farmers were still willing to cultivate cabbage. This result is in line as that of a research by [13] that the suitability level of Mendong plants with the local culture was high because the farmers considered Mendong plants to be ancestral heritage that had to be preserved. This is evident from the fact that even though the land area reduced and the price of mendong fell, the farmers continued to cultivate it.…”
Section: Relatedness Needssupporting
confidence: 90%
“…Fortunately, water in this region is always available in accordance with the needs of farming even in the dry season. A research by [13] showed that there was abundant water in Minggir Subdistrict area for Mendong farming, but the irrigation channel was still centralized in one area and the area never experienced drought despite the dry season.…”
Section: Relatedness Needsmentioning
confidence: 99%
“…Berdasarkan hasil survei yang telah dilakukan, sebanyak 21 petani responden HKm Bina Wana memiliki umur produktif kerja yaitu 15-64 tahun. Hal ini mengacu pada penelitian Nurdina et al (2015) yang mengkategorikan tenaga kerja berdasarkan umur, yaitu belum produktif (0-14 th), produktif (15-64 th), sudah tidak produktif (>65 th). Tingkat pendidikan mayoritas petani responden adalah tingkat SMA sebesar 34% dan minoritas petani responden adalah tingkat Sarjana hanya sebesar 8%.…”
Section: A Karakteristik Petani Responden Hkmunclassified
“…Tingkat Motivasi petani dalam mengelola hutan rakyat menurut Nurdina et al (2015) Nurdina dkk (2015) menunjukkan yang bergabung dalam kelompok tani Ngudi Rukun Memiliki tingkat motivasi tinggi sebesar 53,15% dalam pengelolaan hutan rakyat. Hasil penelitian Abdullah (2013) menyatakan bahwa terdapat hubungan secara nyata faktor umur, pendidikan formal, pendidikan non formal, pengalaman , frekuensi mengikuti penyuluhan dan modal usahatani dengan kompetensi petani rumput laut.…”
Section: Pendahuluanunclassified